Evaluation of Neuropathological Features in the SOD1-G93A Low Copy Number Transgenic Mouse Model of Amyotrophic Lateral Sclerosis - Molnar-Kasza, Agnes; Hinteregger, Barbara; Neddens, Joerg; Rabl, Roland; Flunkert, Stefanie; Hutter-Paier, Birgit (Frontiers in Molecular Neuroscience, 2021)
Amyotrophic lateral sclerosis still depicts an incurable and devastating disease. Drug development efforts are mostly based on SOD1-G93A mice that present a very strong and early phenotype, allowing only a short time window for intervention. An alternative mouse model is available, that is based on the same founder line but has a reduced SOD1-G93A copy number, resulting in a weaker and delayed phenotype. To be able to use these SOD1-G93A/low mice for drug testing, we performed a characterization of ALS-typical pathologies. All analyses were performed compared to non-transgenic littermates of the same sex and age. In vivo analysis of SOD1-G93A/low mice was performed by weekly body weight measurements, analysis of the survival rate and measurement of the muscle strength of 24 to 30 weeks old female and male SOD1-G93A/low mice. Immunofluorescent labeling of SOD1, GFAP and Iba1 protein was performed in the cervical, thoracic, and lumbar ventral horn of the spinal cord of 24 to 30 weeks old male and female SOD1-G93A/low mice. The musculus gastrocnemius of male SOD1-G93A/low mice was labeled with fluorophore conjugated α-bungarotoxin and antibody against phosphorylated neurofilaments. Fluorescent labeling was detected and quantified by macro-based image analysis. Although SOD1 protein levels were highly increased in both sexes and all age groups, levels strongly peaked in 30 weeks old male SOD1-G93A/low mice. Astrocytosis and activated microglia in the spinal cord ventral horn and phosphorylated neurofilaments in the motor unit of the musculus gastrocnemius progressively increased while muscle strength progressively decreased in male SOD1-G93A/low mice. In female SOD1-G93A/low mice, only activated microglia increased progressively while muscle strength was constantly reduced starting at 26 weeks. These differences result in a shorter survival time of male SOD1-G93A/low mice of about 3 weeks compared to female animals. Our results suggest, that male SOD1-G93A/low mice present a stronger pathology and are therefore better suitable to evaluate the efficacy of new drugs against ALS as most pathological features are developing progressively paralleled by a survival time that allows a treatment start before symptom onset.